THE TRANSFORMATION OF CINEMATOGRAPHY STYLE IN INDONESIAN CINEMA IN THE DIGITAL ERA - Denny Setiawan Batubara; Tuty Mutiah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The development of digital technology has brought significant changes to various aspects of the film industry, including cinematography. Cinematography, as an essential element in filmmaking, plays an important role in delivering messages, building atmosphere, and creating visual experiences for audiences. This study aims to analyze the transformation of cinematographic styles in Indonesian cinema in the digital era and to identify the impact of technological development on camera techniques, lighting, visual composition, and post-production processes. This research employs a qualitative method with a descriptive approach through a literature review of various journals, books, scientific articles, and relevant sources discussing the development of cinematography and Indonesian cinema. The collected data were analyzed to identify changes in visual styles before and after the adoption of digital technology in film production. The results of the study indicate that the digital era has driven a transformation toward more dynamic, flexible, and innovative cinematographic styles. The use of high-resolution digital cameras, drone technology, camera stabilization devices, and modern editing software enables Indonesian filmmakers to produce higher-quality visuals with more efficient costs. In addition, digital technology also provides opportunities for filmmakers to explore more creative visual styles that align with the narrative needs of films. Thus, the transformation of cinematographic styles in Indonesian cinema during the digital era not only improves the technical quality of film production but also expands artistic possibilities in storytelling for audiences.